High employment generating industries in Portugal : an input-output approach - Lopes, João Carlos (2012)
An increase in the unemployment rate is one of the most serious consequences of macroeconomic crises. In Portugal, the impact of the deep recession of 2009 has been particularly strong. In this paper, after quantifying this macroeconomic problem, an input-output approach is used in order to identify the high employment generating (or destructing) industries. This approach is particularly interesting because it considers not only the direct flows of job creation and destruction, but also the employment changes attributable to the indirect and induced effects of interindustry connections (the flows of intermediate inputs’ supply and demand). Using the so-called hypothetical extraction (or “shut-down of industry”) method and the employment and input-output data of the Portuguese economy, the key sectors in terms of multipliers, elasticities and the creation of jobs are identified. The empirical results of this paper can be useful in improving the policy responses to the crisis and implementing the most appropriate measures to stimulate the economy.